The Kecemasan di novel Meena Kandasamy When I Hit You - Sodikin; Suhandoko, Khairunissya Turachma Aurelly Nurananda; Sodiq, Machfud Muhamad; Efendi, Nasikul Mustofa; Fanani, Abu (Universitas Nusantara PGRI Kediri, 2023)
This study aims to explain the anxiety of Meena, the main character in When I Hit You novel. This study focuses on how the anxiety is experienced by the main character in the novel. Using the types of anxiety as well as descriptive qualitative methods, the writer finds that Meena as the main character in the novel experiences three types of anxiety which are neurotic anxiety, moral anxiety, and realistic anxiety. The types of anxiety experienced by Meena can be seen in the feeling of tense and restless, the feeling of shame, guilt and worry, and also the fears of her abusive husband.